2015
DOI: 10.3923/ajas.2015.280.292
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphological and Histochemical Studies of the Stomach of the Mallard (Anas platyrhynchos)

Abstract: The study aimed to find out the histomorphological and histochemical structures of the walls of the stomach parts in mallard. To conduct this investigation, twelve healthy birds were collected from local suppliers at Baghdad province. Later on, birds were subdivided into three equal subdivisions, each of four for gross, histological and histochemical approaches. All birds were anesthetized and their abdomens were dissected, then their stomach were identified and photographed in situ. Organs were grossly descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 13 publications
3
9
0
Order By: Relevance
“…The location of the deep proventricular glands within the proventricular wall remains controversial; the current investigation revealed that these glands were located in the tunica submucosa. This result was in accordance with Selvan et al (2008) and Al-Saffar and Al-Samawy (2015) in the mallard and Batah et al (2012) in the coot bird, who reported the same site of the deep proventricular glands.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The location of the deep proventricular glands within the proventricular wall remains controversial; the current investigation revealed that these glands were located in the tunica submucosa. This result was in accordance with Selvan et al (2008) and Al-Saffar and Al-Samawy (2015) in the mallard and Batah et al (2012) in the coot bird, who reported the same site of the deep proventricular glands.…”
Section: Discussionsupporting
confidence: 92%
“…The location of the deep proventricular glands within the proventricular wall remains controversial; the current investigation revealed that these glands were located in the tunica submucosa. This result was in accordance with Selvan et al (2008) and Al‐Saffar and Al‐Samawy (2015) in the mallard and Batah et al (2012) in the coot bird, who reported the same site of the deep proventricular glands. In contrast to these results, Ogunkoya and Cook (2009) and Sayrafi and Aghagolzadeh (2019) reported two different locations, within the lamina muscularis mucosa and in the lamina propria, respectively.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Al-Saffar & Al-Samawy, 2015;El-Shammaa, El-Sakhawy, EL-Leithy, & Youssef, 2019;Kadhim et al, 2011;Sayrafi & Aghagolzadeh, 2020;Zhu, 2015a).…”
mentioning
confidence: 99%
“…The mucosa consisted simple columnar epithelium in the form of short folds confined by gastric pits. The lamina properia contained simple tubular glands that open at the base of the gastric pits among folds and fill the cavity with koilin, which is consistent with (18). The koilin appears to be positive for AB/PAS stain, because koilin is protein-like substance (16,19).…”
Section: Resultsmentioning
confidence: 61%